Frequency & Probable Risk Factors of Anemia In Last Trimester Among Pregnant Women - Sarnina Radar, M. Siddique Khan Qadri, Huda Abbas, Wajahat Hussain (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
(AM-lye: To determine the frequency and probable risk factors of anemia in last trimester among pregnant women visiting Gynecology and Obstetrics outpatient department of Bahawal ’Victoria Hospital Bahawalpur. Study Design: Cross-sectional descriptive study Place & Duration: Outpatient department of Gynecology and Obstetrics. Bahawal Victoria Hospital Bahawalpur, from January to December 2014. Material & Methods: The women in third trimester of pregnancy, of any age and parity with singleton pregnancy visiting the outpatient department were included in the study. The exclusion criteria was unwilling women, history of blood transfusion within last three months, taking iron supplement with history of co-morbidities like diabetes mellitus, hypo or hyperthyroidism, cardiac diseases, connective tissue disorders and chronic renal disease. Data was collected by using preformed, pretested questionnaire. Hemoglobin (Hip) level of each women was determined by collecting 2m1 of venous blood into tubes with EDTA and sending them to laboratory of pathology department Quaid-e-Azam Medical College Bahawalpur for estimation of hemoglobin, Respondents were categorized into three groups according to their per month family income. Respondents were asked about frequency of taking meat, egg. fruit, soft drink, fried food, baked food and salad as part of their meal and response was categorized into daily intake: Use daily in one meal per day, occasional intake: 3 days in a week in one meal per day and often: 3-6 days in a week in one meal per day. All the data collected was statistically analyzed & results were tabulated. Results: Total 2356 pregnant women were included in the study. The mean age of respondents was 242.3 years. The anemia was detected among 28.1% in the last trimester of pregnancy. Out of all anemic women. 14.05".0 belongs to age group of 15-20 years, 35.04% to 21-25 year 33.84% to 26-30 years and 17.07% to 31 years. About 63.8% anemic women belonged to low socio-economic status. 33.1% belongs to middle and 3 % had high socio-economic scams. About 63.81)/6 anemic women belonged to extended family system, 34.4°) nuclear and 1.8°’. were from polygamous family. In 81.5% anemic women, 60.7% were illiterate, 28.3"...0 had education up to matric and 11% were above matric and 44.7% husbands of these anemic women were illiterate, 40.6% were educated up to matric and 13.7% having education above matric. It is seen that 25.4% anemic women have I-2 children. 3,1..6% have 3-4 children and 40% have 5 children. Daily consumption of meat, egg, fruits, soft drinks, fried food. vegetable and salad was 17%, 13%, 37%, 69%, 71%, 71°’0 and 23"/i) respectively in the females having anemia (hemoglobin level <1 lgin/d1) as compared to 31%, 44%, 49%, 11%, 12%, 13% and 77% respectively in non-anemic females (hemoglobin level >1 lgmidl ). Conclusion: It is concluded that prevalence of anemia is high in last trimester of pregnancy, and is inversely proportional to education of female, family income, parity and also seen high in extended family.